A phospholipid polymer graft layer affords high resistance for wear and oxidation under load bearing conditions. (March 2018) - Kyomoto, Masayuki; Moro, Toru; Yamane, Shihori; Watanabe, Kenichi; Hashimoto, Masami; Tanaka, Sakae; Ishihara, Kazuhiko
Abstract: Manipulating the surface and substrate of cross-linked polyethylene (CLPE) is an essential approach for obtaining life-long orthopedic bearings. We therefore proposed a bearing material comprised of an antioxidative substrate generated by vitamin E blending (HD-CLPE[VE]) with a poly(2-methacryloyloxyethyl phosphorylcholine) (PMPC)-grafted surface, and investigated its wear resistance and oxidative stability under accelerated aging and load bearing conditions. Neither the hydration nor friction kinetics of the molecular network structure of the PMPC-grafted surface or the HD-CLPE(VE) substrate were influenced by accelerated aging but rather exhibited high stability even under high oxidation conditions. The characteristics of the PMPC-grafted surface improved the wear and impact fatigue resistance of the HD-CLPE(VE) liner regardless of accelerated aging. Notably, the PMPC-grafted surface was found to affect the potential oxidative stability at the rim part of the acetabular liner. PMPC chains serve several important functions on the surface regardless of load bearing, such as high lubricity or low lipophilicity attributed to phosphorylcholine groups and/or surrounding water-fluid film, and suppression of lipid diffusion attributed to methacrylate main chains on the surface. Together, these results provide preliminary evidence that the PMPC graft layer and vitamin E-blended substrate might positively affect the extent of orthopedic implant durability. Graphical abstract: fx1